Cotton root volume and root dry matter as function of high soil bulk density and soil water stress - Duruoha, Charles; Piffer, Cassio Roberto [UNESP]; Silva, Paulo Roberto Arbex [UNESP] (My University, 2008)
Soil compaction reduces root growth, affecting the yield, especially in the Southern Coastal Plain of the USA. Simulations of the root restricting layers in greenhouses are necessary to develop mechanisms which alleviate soil compaction problems. The selection of three distinct bulk densities based on the Standard Proctor Test is also an important factor to determine which bulk density restricts root penetration. This experiment was conducted to evaluate cotton (Gossypium hirsutum L.) root volume and root dry matter as a function of soil bulk density and water stress. Three levels of soil density (1.2, 1.4, and 1.6 g cm-3), and two levels of water content (70 and 90% of field capacity) were used. A completely randomized design with four replicates in a 3×2 factorial pattern was used. The results showed that mechanical impedance affected root volume positively with soil bulk density of 1.2 and 1.6 g cm-3, enhancing root growth (P>0.0064). Soil water content reduced root growth as root and shoot growth was higher at 70% field capacity than that at 90% field capacity. Shoot growth was not affected by the increase in soil bulk density and this result suggests that soil bulk density is not a good indicator for measuring mechanical impedance in some soils.
Keywords: Root growth; Soil density; Water stress; bulk density; cotton; dry matter; root; shoot growth; soil property; water stress; Gossypium hirsutum